Flow cytometric analysis of innate lymphoid cells: challenges and solutions - Sadeghalvad, Mona; Khijakadze, Davit; Orangi, Mona; Takei, Fumio (Frontiers in Immunology, 2023)
The three groups of helper innate lymphoid cells (ILCs), namely ILC1, ILC2 and ILC3, have been identified by flow cytometry by combinations of cell surface markers. Here, we review various ways ILCs are currently identified, focusing on potential problems and their solutions. The first step to identify all ILCs is to exclude other lymphocytes and myeloid cells by their lineage specific markers (Lin). However, the Lin cocktail varies in various studies, and the definition of Lin -population containing ILCs is often ambiguous, resulting in contamination of Lin + cells, particularly T cells. Each ILC population is also heterogenous and cell suface marker expression varies among ILCs in different tissues. Here, we have designed combinations of cell surface markers to identify ILC populations in various tissues. To minimize T cell contamination, TCR/CD3ε antibodies were used separately from the Lin cocktail. ILCs identified by surface markers are confirmed by the expression of the transcription factors GATA3, RORt, T-bet and Eomes. ILC1s are identified by Lin -NKp46 + NK1.1 + TCR/CD3ε − CD49a + CD49b − . ILC2s in the lung are identified by Lin − TCR/CD3ε − Thy1 + CD127 + ST2 + whereas ILC2s in the small intestine and liver are identified by Lin − TCR/CD3ε − Thy1 + GATA3 + RORt − . ILC3s are identified by Lin − TCR/CD3ε − Thy1 + CD127 + RORt + . This strategy minimizes contamination of T cells specifically identify individual ILC populations in various tissues.